Agri Digitalization Framework (AgDx) – Methodology Report - Rangrass, Sanjiv; Mehrotra, Nipun; Mehrotra, Navya; Dhulipala, Ram; Singh, Kanika (International Livestock Research Institute, 2024)
The agriculture sector faces significant challenges, including limited access to technology, markets, and finance for small farmers. Accelerating digitalization can improve productivity, reduce wastage, and support food security while protecting the environment. With the digital agriculture market in India projected to reach $24 billion by 2025, collaboration across stakeholders is vital. To aid this, the Digital Innovation Initiative, in partnership with The Agri Collaboratory (TAC), is developing the Agri Digitalisation Framework (AgDx), a farmer-first index to evaluate the penetration, maturity, and impact of digital agriculture practices across states and value chains. Standardized frameworks and benchmarks like AgDx are essential to reduce duplication and help expand digital adoption from 15-20% to 50% among farmers